The Development of Adolescent Wirid Models in Fostering Character Using Local Wisdom Approaches in the City of Padang - Slamet Riyadi; Syafruddin Nurdin; Duski Samad (Global Writing Academica Researching & Publishing, 2022)
Wirid teenagers in the city of Padang exist as a non-formal educational institution to overcome the problem of the lack of hours of religious and moral learning in formal schools. The Mayor of Padang Instruction Number 451,286 of 2012 is the legal basis for youth wirid activities in Padang, with obligations imposed on students of SMP/MTs in the city of Padang. This youth wirid activity is expected to improve the practice of Islam and character in the lives of teenagers who are centered in the mosque. This is in line with the concept of the Minangkabau people's life, which is rich with local wisdom; to shape the character of the younger generation, it is necessary to develop youth wirid activities in shaping character. With a local wisdom approach in the city of Padang. This development is carried out in the form of its application both from the curriculum, materials, methods, and adolescent wirid its relation to religion at school and home, from two places as control and experimental classes—adolescent character, which is following Minangkabau customs.